The dopamine D3 receptor gene: no association with bipolar affective disorder. Issue 4 (April 1993) - Shaikh, S; Ball, D; Craddock, N; Castle, D; Hunt, N; Mant, R; Owen, M; Collier, D; Gill, M
Abstract : Bipolar affective disorder and schizophrenia share many clinical and genetic characteristics, and are thought by some to be different expressions of the same underlying disorder. A recent study showed an excess of homozygosity at a BalI polymorphism in the dopamine D3 receptor gene in schizophrenic patients compared with controls, from two independent centres. We have found no evidence of such an excess in a comparable sample of patients with bipolar affective disorder compared with matched controls. If these findings are confirmed then at least one genetic distinction between these two disorders will have been ascertained and doubt cast upon theories of a common genetic aetiology.